2022
DOI: 10.56556/jssms.v1i2.48
|View full text |Cite
|
Sign up to set email alerts
|

The significance of confidence and own financial literacy: Gender Diversity in asset behaviour

Abstract: This research paper plays a role in people's self-belief in financial literacy in defining the gender gap in risky assets while managing basic financial information and risk management. It is a leading research article to review the financial viability of a large group of states. This is the opinion to seek the task of self-confidence through anti-corruption strategies. The results from our investigation examine the recent discovery of modern financial systems: confidence in the strong commitment to accounts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Women's employment is growing with the expansion of economic advancement (Kumari, 2018;Hussain & Rasheed, 2022). Several theoretical and experimental studies have shown that the support of women in the workforce has strong and positive links to financial development (Eng, 2006), and a clear correlation between women's interest in the workforce and their financial development is revealed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women's employment is growing with the expansion of economic advancement (Kumari, 2018;Hussain & Rasheed, 2022). Several theoretical and experimental studies have shown that the support of women in the workforce has strong and positive links to financial development (Eng, 2006), and a clear correlation between women's interest in the workforce and their financial development is revealed.…”
Section: Literature Reviewmentioning
confidence: 99%